CORROSION INHIBITION EFFICIENCY, ADSORPTION BEHAVIOR, KINETICS AND THERMODYNAMIC STUDIES OF LANNEA ACIDA ETHANOL LEAVES EXTRACT ON MILD STEEL IN HYDROCHLORIC ACID (FUDMA JOURNAL OF SCIENCES, 2021)
The corrosion inhibition potential of lannea acida (LA) ethanol leaves extract was investigated using mild steel in 1.0 M HCl solution. The leaves extract was characterized using FT- IR Spectroscopy. The surface analysis of the mild steel was also studied using scanning electron microscopy. The study was carried out at an ambient temperature and selected high temperatures. The LA leaves extract concentration ranges from 0.1- 0.9g/L. The data obtained from weight loss measurements show that the leaves extract repressed the corrosion rate of mild steel. The increase in temperature with a corresponding increase or decrease in the inhibitor efficiency of LA leaves extract shows that the adsorption mechanism obeyed comprehensive adsorption. The value of activation energies (Ea) obtained which ranged from 15.32 to 17.63 kJ mol-1 agrees with the physical adsorption mechanism. The values of enthalpy of activation (Î”H*) obtained were positive and ranged from 38.29 to 59.00 KJ mol-1 is an indication that the dissolution of the mild steel is an endothermic reaction and requires less energy in the presence of LA leaves extract. The values of entropy of activation (Î”S*) obtained which were negative indicate that the activated complex in the rate-determining step is associative rather than dissociative. The kinetics study shows the adsorption process follows first-order kinetics. The adsorption isotherm data fitted best into Freundlich adsorption isotherm
Keywords: Corrosion rate, mild steel, HCI, Lannea acida (LA), adsorption, efficiency, temperature